Dual Purpose Summer Mungbean for Sustainable System and Food and Nutritional Security - Sharma, S. N. (Indian Farming, 2015)
Summer mungbean has the potential for sustaining cropping systems, increasing pulse production of the country, enriching the soil, increasing farmers’ incomes and improving diets of the people. The rapid adoption of improved mungbean varieties is a true transformation for a win-win situation for farmers, traders, consumers-especially the poor. The results have shown that this would be a model for the future work in ICAR institutes, SAUs and State agricultural departments.